ØªÙ†Ù…ÙŠØ© Ø§Ù„ÙˆØ§Ø³Ø·Ø© Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© Ø¨Ø¹Ø±Ø¶ ØªÙ‚Ø¯ÙŠÙ…ÙŠ Ø¹Ù„Ù‰ Ù…ÙˆØ§Ø¯ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Suaidi Suaidi (Lughatu Ad-Dhat, 2020)
The research used is Research and Development. Where this method is used to produce certain products and test the effectiveness of these products. This research instrument test uses the validity and reliability test. The results of the validity test of 15 test items, there are 12 valid items and 3 invalid and reliable items with a reliability coefficient of 0.820. Furthermore, the data were tested with the